2022
DOI: 10.3390/ma15207100
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Ceramics with Silver Nanoparticles for Electromagnetic Shielding Applications

Abstract: Ceramic composites with nanoparticles are intensively investigated due to their unique thermal, mechanic and electromagnetic properties. In this work, dielectric properties of phosphate ceramics with round silver nanoparticles of various sizes were studied in the wide frequency range of 20 Hz–40 GHz for microwave shielding applications. The percolation threshold in ceramics is close to 30 wt.% of Ag nanoparticles content and it is higher for bigger-sized nanoparticles. The microwave complex dielectric permitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It can be concluded that the absorption of some of these composite structures is quite high, for example, that of the RC X sample at 35 GHz is 55%. It is comparable to the best absorption of ceramics with SiC or Ag nanoinclusions, or hybrid carbon magnetic/carbon nanostructures [ 26 , 28 , 29 , 30 , 31 , 32 ]. Measurements in different directions reveal strong anisotropy of the electromagnetic response.…”
Section: Resultsmentioning
confidence: 93%
“…It can be concluded that the absorption of some of these composite structures is quite high, for example, that of the RC X sample at 35 GHz is 55%. It is comparable to the best absorption of ceramics with SiC or Ag nanoinclusions, or hybrid carbon magnetic/carbon nanostructures [ 26 , 28 , 29 , 30 , 31 , 32 ]. Measurements in different directions reveal strong anisotropy of the electromagnetic response.…”
Section: Resultsmentioning
confidence: 93%
“…Also, important characteristics in shielding materials are the parameters of resistance to external influences, including mechanical or long-term radiation exposure, which has a cumulative effect. All this, despite the large number of studies in this area, requires new research and experimental confirmation of the efficiency of shielding of new types of materials depending on their composition and applications [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%